Frequency of Postoperative Maxillomandibular Fixation Following Open Reduction and Internal Fixation in Maxillofacial Fractures - Mahrukh Shahbaz; Aqib Sohail; Fareed ud Din Ahmad Chishti; Ali Ammar Hasan; Muhammad Abubakr Bin Nauman; Muneeba Shoaib (Journal of University College of Medicine and Dentistry)
Objective: To determine the frequency of postoperative maxillomandibular fixation (MMF) required after open reduction and internal fixation (ORIF) for restoring premorbid occlusion in patients with maxillary and mandibular fractures.